Back spin - Coben, Harlan, 1962- (Coben, Harlan, 1962- Myron Bolitar novel., 2022)
When veteran golfer Jack Coldren, staging a comeback at the U.S. Open, is found dead in a sand trap, sports agent Myron Bolitar investigates, digging through twenty years of secrets to find a killer who is closer to him than he imagined.